PERTUMBUHAN RUMPUT LAUT (Eucheuma cottonii) PADA KEDALAMAN AIR LAUT YANG BERBEDA DI DUSUN KOTANIA DESA ETI KECAMATAN SERAM BARAT KABUPATEN SERAM BAGIAN BARAT - Wa Surni (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Background: cottonii Eucheuma Seaweed is macro algae that live in the sea, generally in the bottom waters and attached to the substrate or other objects and also life floating on the sea surface. Part - part seaweed generally consists of Holdfast is a basic part of the seaweed that serves to attach to the substrate and thalus which forms the growth of seaweed that resembles branching. Seaweed growth is highly dependent on factors oceanography (physics, chemistry, and dynamics of movement or sea water), seaweed take nutrients from the surroundings by diffusion and osmosis through thallus wall. Methods: Based on the results of research conducted in June 2011, and then do an in-depth study related to planting seaweed Eucheuma cottonii with different depths - the difference of up to 30 cm, 40 cm, and 50 cm in the village kotania coastal waters. Results: The results showed that at a depth of 30 cm of growth is very good compared to the depth of 40 cm and 50 cm less growth in both .This can be caused due to the presence of light intensity on the surface of the sea water in comparison with the deeper parts. Conclusion: The depth is good for the growth of seaweed is 30 cm below sea level with an average wet weight for 35 days (5 weeks) is 160 grams